2013
DOI: 10.4269/ajtmh.12-0628
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Horizontal Approach in Vertical Program: Continuous Quality Improvement of Malaria and Tuberculosis Diagnostic Services at Primary-Level Medical Laboratories in the Context of HIV Care and Treatment Program in Ethiopia

Abstract: Abstract. The use of standardized tools for continuous quality improvement of laboratory services is crucial to identify service gaps, plan targeted interventions, and prove successes. Laboratory quality improvement tools (LQITs) were developed and applied for 18 months at five health centers and one faith-based hospital laboratories in Southwest Showa Zone in Ethiopia to assess and monitor the quality of malaria and acid-fast bacilli (AFB) microscopy total testing processes. For the six laboratories, baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Over the past decade, the WHO and other organizations in the field have given much attention to the issue of health systems strengthening [ 7 , 14 , 28 30 ] and the government of Ethiopia has been in the loop reaffirming its commitments and consolidating the gains [ 10 , 13 , 31 – 33 ]. This study deepens understanding of how healthcare facilities can develop a platform to assess and monitor their performances for on-going improvements in the context of the WHO’s six health system building blocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, the WHO and other organizations in the field have given much attention to the issue of health systems strengthening [ 7 , 14 , 28 30 ] and the government of Ethiopia has been in the loop reaffirming its commitments and consolidating the gains [ 10 , 13 , 31 – 33 ]. This study deepens understanding of how healthcare facilities can develop a platform to assess and monitor their performances for on-going improvements in the context of the WHO’s six health system building blocks.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate the WHO health system framework is instrumental in strengthening the overall health system and uses as catalyst for achieving global health targets such as the SDGs. Unlike other health system strengthening strategies which are disease-specific [ 13 ] or narrow [ 14 16 ], the WHO’s health system framework intends to improve the overall health in a responsive, financially fair and most efficient way [ 11 ]. Evidences revealed that the framework helps to assess in-country healthcare performances [ 17 ], interactions between health reforms and country health systems [ 18 ], implications of health sector reforms [ 19 ], and the status of health facilities [ 20 ] and specific health problems [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the same-day microscopy intervention targeted two crucial areas of the diagnostic pathway: testing completion and treatment initiation. Many studies concentrate on improving a single element of the diagnostic pathway, such as laboratory performance or reporting of smear results [ 21 , 33 , 34 , 35 , 36 , 37 ]. While these strategies may have an impact, approaches that influence multiple barriers are likely more effective [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other needs and gaps, including rehabilitation of facilities, provision of continuous water and electricity, and provision of laboratory personnel will need additional financial investment. Together with the continued roll-out of multispecies RDTs at community level, it is hoped that increasing the laboratory capacity of health facilities through QA programmes [ 27 ] will ensure that fever cases in Ethiopia are increasingly accurately diagnosed. This should increase health service delivery overall, access of facilities by patients, as well as decrease the total cost of diagnosis and treatment (potentially by up to 46%) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%